Luminescence properties of YVO4: Ln (Ln = Dy3+, Eu3+, Tm3+) for white LED by hydrothermal method. (September 2018) - Shao, Jingyu; Liu, Chunpeng; Zhou, Xuan; Hong, Luying; Yan, Jinghui; Kang, Zhenhui
Abstract: YVO4 : Dy 3+, Eu 3+ / YVO4 : Dy 3+, Eu 3+, Tm 3+ phosphors were synthesized by a simple hydrothermal method. The energy transfer from Dy 3+ to Eu 3+ was determined by photoluminescence (PL) spectra and fluorescence lifetime. The energy transfer mechanism from Dy 3+ to Eu 3+ was confirmed. The amount of Eu 3+ in YVO4 : 0.01Dy 3+, Eu 3+ with strong emission and small size was determined by applied ratio, and finally a white light (0.300, 0.317) output was achieved in YVO4 : 0.01Dy 3+, 0.01Eu 3+, 0.03Tm 3+ by adjusting the amount of activator ions. Thus the sample with the above characteristics has a promising application prospect in the light emitting diode (LED).